Influence of bamboo pile clusters in the pile mattress bamboo construction systems as reinforcement of soft subgrade that support embankment load. (May 2019) - Widodo, B; Pratikso; Rochim, A; Irsyam, M; Widoanindyawati, V
Abstract: One of the problems that arise in building land transport infrastructure located on soft soil is the making of the road construction. The completion of the road construction issue is carried out by the engineering that the road is safe and stable. The main long-term goal of this research is to provide a method of handling embankment construction that is above soft soil, complementing the existing methods, by using the main bamboo material. This study discussed the influence of bamboo pile clusters on a bamboo matrass construction system to support the embankment load on soft soil. The method of this research is to make a bamboo cluster containing 3 bamboo sticks, 4 bamboo sticks, and 7 bamboo sticks. The cluster is inserted into the soft soil. Bamboo pile clusters are gradually loaded until the soil collapses. Data that is investigated in the area of the cluster and the force given to suppress the cluster. The results of the study show the relationship of bamboo pile clusters with Pult . The value of the P ult depends on the area of the cluster with the formula: P ult = 840 L n ( X ) - 3044 with X = is the cluster area.